Data from: Arsenic bioaccumulation in subarctic fishes of a mine-impacted bay on Great Slave Lake, Northwest Territories, Canada ... - Chételat, John; Cott, Peter A.; Rosabal, Maikel; Houben, Adam; McClelland, Christine; Belle Rose, Elise; Amyot, Marc (Dryad, 2019)
A subarctic fish community in mine-impacted Yellowknife Bay (Great Slave Lake, Northwest Territories, Canada) was investigated for biological and ecological processes controlling arsenic bioaccumulation. Total concentrations of arsenic, antimony, and metals were measured in over 400 fishes representing 13 species, and primary producers and consumers were included to characterize food web transfer. Yellowknife Bay had slightly more arsenic in surface waters (~3 µg/L) relative to the main body of Great Slave Lake (<1 µg/L), resulting in two-fold higher total arsenic concentrations in muscle of burbot (Lota lota), lake whitefish (Coregonus clupeaformis), and northern pike (Esox lucius). Other mining-associated contaminants, specifically antimony, lead, and silver, were typically below analytical detection in those fish species. No evidence was found for enhanced bioaccumulation of arsenic in long-lived, slow-growing subarctic fishes. Food web biodilution of total arsenic occurred between primary producers, ... : Dryad Dataset_PLOS ONE_Great Slave Lake Fish Metal(loid)sThis file contains measurements of metal(loid) concentrations and ancillary data for fishes of Great Slave Lake, Northwest Territories, Canada. The worksheets contains: (1) Locations of fishes captured during the study; (2) Size, age, metal(loid) concentrations, and carbon and nitrogen stable isotopes of fishes captured for the study; (3) Size, age, and metal(loid) concentrations of fishes reported in 2 grey literature technical reports on the study area; (4) Size and metal(loid) concentrations of fishes examined in a previous publication (Cott et al. 2016.Journal of Great Lakes Research 42(2):223-32). ...